ANALISIS FLUKTUASI DAN ELASTISITAS TRANSMISI HARGA KENTANG DI KABUPATEN MAGELANG - Nun Maulida Suci Ayomi; Bambang M. Setiawan; Wiludjeng Roessali (JURNAL LITBANG PROVINSI JAWA TENGAH, 2020)
The price difference was received by farmers and the price was paid by consumers indicates that the price paid by consumers is not the price received by farmers. This study aims to analyze the price fluctuation and elasticity of price transmission potato in Magelang Regency. This research have secondary data during 156 weeks on 2016 until 2018. An instrument analyze used coefficient of variation for price fluctuation and simple linier regression for elasticity of price transmission. The results of research revealed that value coefficient of variation 15,70% this mean price fluctuation potato in Magelang Regency was high, and elasticity of price transmission potato was small (ƞ = 0,950) is inelastic (E <1) which means the sensitivity of price changes at the farm level is smaller than the price change at the merchant level. Decreasing potato in production was resulted in impact of the price of potato which was uncertain from season to another season. The long marketing chain affects elasticity of price transmission. Farmers who act as price taker, only received the price that has been given by the village collectors.